Ethics and Expertise: A Social Networks Perspective - Lee, Seung Hwan Mark (2013)
Results from three field network studies show that depending on individuals’ network positions (central or peripheral), experts and novices have varying ethical predispositions (EP). In particular, central experts (vs. peripheral experts) have higher EP, while novices in the same positions (vs. peripheral novices) have lower EP. Results demonstrate individuals’ relational-interdependent self-construal mediates these relationships. Importantly, this research suggests that the interaction between network and individual difference variables uniquely affect individuals’ ethical predisposition. Given the lack of research focus on the impact of structural positions on EP, this article demonstrates the importance of combining network and individual variables to investigate individuals’ EP.
Keywords: network centrality; Ethical Predisposition; Novices; Experts